Design of T-shaped UWB antenna with dual band rejection using inverted u- and c-shaped slots - Salwa, Awang Akbar; Ahmad Syahiman, Mohd Shah; Ahmad Afif, Mohd Faudzi; Sabira, Khatun; Syamimi Mardiah, Shaharum; Nurhafizah, Abu Talip; Mohamad Shaiful, Abdul Karim (Springer Singapore, 2018)
An ultra-wideband antenna design is proposed in this paper based on simple and easy-fabricated rectangular patch antenna. The proposed antenna is inserted with two slots; inverted U- and C-shaped to minimize interference in WiMax and WLAN band. The antenna can afford a good range of operating fre-quency from 2.852 GHz to 12.176 GHz, which covers ultra-wideband frequency range set by Federal Communication Commission and in the same time be able to avoid undesired band.